ASPEK-ASPEK SOSIAL SATUA MEKEL PARIS, JACKRIS, DAN MADE SMITH DALAM PUPULAN SATUA BALI MODERN MEKEL PARIS KARYA I.B.W. WIDIASA KENITEN PENDEKATAN SOSIOLOGI SASTRA - Arista, Kadek Eva (Humanis; Volume 7. No. 1. April 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 This research study about Mekel Paris short story, Jackris short story, and Made Smith short story, gathered in Mekel Paris short story corps. This Research aim to know the aspect of social exist in this short story. Basis for used by theory is sociology theory. The method that used there is three for example, ready Phase of data use method read, phase analyse data by using method qualitative, and presentation phase result of data analysis use informal method. Result of which is obtained in this research that is expressing of of social, becoming object from this research for example: aspect of marriage, aspect of naming is name, aspect of heritage, and my me aspect of social ethics / ethic. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: short story and social aspect